Integrating Real-World Motion: Physics Behind Racing Motorbikes at Mandalika - Safitri, Afaurina Indriana; Admoko, Setyo; Dawana, Irgy Redityo (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
This research aims to explore physics concepts involved in motorcycle racing and apply the analysis results as a fun physics learning media. This research is exploratory research with literature study and race video analysis by integrating literature study to strengthen the research. We explore vehicle dynamics, kinematics, aerodynamics, engine mechanics, thermodynamics, and other physics concepts relevant to motorcycle racing at Mandalika Circuit through a physics perspective analysis approach. This research includes an in-depth physics analysis of racing bikes and explores the implications of the results of this research for physics education. The results show that racing bikes, especially when used at Mandalika Circuit, provide authentic content to apply physics concepts in an engaging way for students. The implication of this research to physics learning is that motorcycle racing at Mandalika Circuit provides an interesting context to apply physics concepts such as dynamics, aerodynamics, and thermodynamics. By utilizing concrete examples from motorcycle racing at Mandalika Circuit, physics learning can be enhanced, arouse learners' interest, and strengthen their understanding of basic physics concepts.